Waterfowl in Cuba: current status and distribution - Rodríquez, Pedro Blanco; Vilella, Francisco J.; Oria, Bárbara Sánchez (Wildfowl, 2014)
Cuba and its satellite islands represent the largest landmass in the Caribbean archipelago and a major repository of the region’s biodiversity. Approximately 13.4% of the Cuban territory is covered by wetlands, encompassing approximately 1.48 million ha which includes mangroves, flooded savannas, peatlands, freshwater swamp forests and various types of managed wetlands. Here, we synthesise information on the distribution and abundance of waterfowl on the main island of Cuba, excluding the numerous surrounding cays and the Isla de la Juventud (Isle of Youth), and report on band recoveries from wintering waterfowl harvested in Cuba by species and location. Twenty-nine species of waterfowl occur in Cuba, 24 of which are North American migrants. Of the five resident Anatid species, three are of conservation concern: the West Indian Whistling-duck Dendrocygna arborea (globally vulnerable), White-cheeked Pintail Anas bahamensis (regional concern) and Masked Duck Nomonyx dominicus (regional concern). The most abundant species of waterfowl wintering in Cuba include Blue-winged Teal A. discors, Northern Pintail A. acuta, and Northern Shoveler A. clypeata. Waterfowl banded in Canada and the United States and recovered in Cuba included predominantly Blue-winged Teal, American Wigeon and Northern Pintail. Banding sites of recovered birds suggest that most of the waterfowl moving through and wintering in Cuba are from the Atlantic and Mississippi flyways. Threats to wetlands and waterfowl in Cuba include: 1) egg poaching of resident species, 2) illegal hunting of migratory and protected resident species, 3) mangrove deforestation, 4) reservoirs for irrigation, 5) periods of pronounced droughts, and 6) hurricanes. Wetland and waterfowl conservation efforts continue across Cuba’s extensive system of protected areas. Expanding collaborations with international conservation organisations, researchers and governments in North America will enhance protection of waterfowl and wetlands in Cuba.